Mycoremediation Performance of Pleurotus ostreatus on Mercury- Contaminated Soil using Rice Straw and Sawdust as Substrate - Hakeem Perwira, Evan
Mycoremediation is an alternative method to remediate mercurycontaminated soil. Pleurotus ostreatus (oyster mushroom) is a suitable agent due to its ability to accumulate high concentration of mercury. Mercury has deleterious effects on P. ostreatus’ ability to utilize substrate, therefore substrate formulation becomes a primary concern. This research aimed to evaluate growth and mycoremediation performance of P. ostreatus on mercury-contaminated soil. Substrate compositions of whole rice straw (100%), whole sawdust (100%) and equal mix of both (50:50) were used to cultivate P. ostreatus. Growth performance was analyzed based on rate of substrate colonization, total duration of growth and biomass productivity; while mycoremediation performance analysis was based on soil toxicity level, mercury bioaccumulation and removal. Highest colonization rate was observed in mixed substrate (6,9 mm/day) compared to sawdust (6,2 mm/day) and rice straw (6,0 mm/day). Mixed substrate also required shorter growth time (39,8 days) compared to sawdust (44,9 days) and rice straw (60,7 days). On the other hand, cultivation on rice straw produced highest dry weight than mixed substrate and sawdust, with values of 8,4 g, 5,1 g, and 3,3 g respectively. Mycoremediation on mixed substrate resulted in highest mercury accumulation of 123,60 ?g compared to sawdust (89,89 ?g) and rice straw (82,00 ?g). Observations on mercury removal and soil toxicity indicated similar data trend. Highest merucry removal was achieved on mixed substrate (59,1%) compared to sawdust (46,9%) and rice straw (48,6%). Highest decrease in soil toxicity level was also observed on mixed substrate (26,9%) compared to sawdust (25,0%) and rice straw (22,2%). It was concluded that mixed substrate produced highest growth rate and mycoremediation performance of P. ostreatus compared to other substrate compositions.